The globby1-1 (glo1-1) mutation disrupts nuclear and cell division in the developing maize seed causing alterations in endosperm cell fate and tissue differentiation. - Costa, L; Gutierrez-Marcos, J; Brutnell, T; Greenland, A; Dickinson, H (2003)
Cereal endosperm tissues account for most of the world's calorific intake, yet the regulation of monocot seed development remains poorly understood. The maize endosperm originates with a series of free-nuclear divisions, followed by cellularisation and subsequent formation of a range of functional cellular domains. We describe the isolation and characterisation of a mutation that induces aberrant globular embryo and endosperm morphology, globby1-1 (glo1-1). Our data indicate that glo1-1 plays a role in nuclear division and cytokinesis in the developing seed. Pattern formation in the embryo is severely impaired with development arresting at premature stages, while in the endosperm, the effects of the glo1-1 mutation are manifest at the free-nuclear or syncytial stage. During cellularisation, and at later stages of development, aberrant cell division and localised domains of cell proliferation are apparent in glo1-1 endosperms. As a consequence, cell fate acquisition and subsequent differentiation of endosperm tissues are affected to varying degrees of severity. To date, it has been hypothesised that BETL cell fate is specified in the syncytium and that cell files subsequently develop in response to a gradient of signal(s) derived from the maternal pedicel region. Based on our findings, however, we propose that specification of BETL cells is an irreversible event that occurs within a narrow window of syncytial development, and that BETL cell identity is subsequently inherited in a lineage-dependent manner. Additionally, our data suggest that acquisition of aleurone cell fate does not solely rely upon signalling from the maternal surrounding tissue to the periphery of the endosperm, as previously thought, but that other factor(s) present within the endosperm are involved.